Desarrollo en torno a la protección de datos personales en supuestos de transferencia de cartera crediticia a entidades no supervisadas - Sánchez Concha, Carlo Fabricio (2021)
This article aims to develop the contingencies and possible solutions around the protection of personal data of financial entities’ clients when their credit is transferred to an unsupervised company. This as a result of the inquiry made by the Superintendency of Banking, Insurance and Pension Fund Private Management Firms —SBS— to the Personal Data Authority.